Visual Acuity in Aniridia and WAGR Syndrome - Krause, Michael A; Trout, Kelly L; Lauderdale, James D; Netland, Peter A (Clinical ophthalmology (Auckland, N.Z.), 2023)
Our purpose was to evaluate visual acuity in aniridia subjects and the more severely affected phenotype in WAGR syndrome subjects, and to assess potential impact on visual function. This was a retrospective comparative study of 25 aniridia subjects with nonsense mutations of PAX6 (50 eyes) and 25 WAGR syndrome subjects with large deletion mutations involving PAX6 (50 eyes). Aniridia subjects were age- and gender-matched with WAGR syndrome subjects in the Coordination of Rare Diseases at Sanford (CoRDS) database. Best-corrected ETDRS visual acuity measurements were converted to LogMAR visual acuity values, which were used to perform statistical analyses. The age and gender distribution of the subjects was not statistically significantly different. The mean LogMAR values in aniridia and WAGR syndrome subjects were 0.95±0.53 and 1.51±0.99, respectively (P<0.001). In the better-seeing eye, mean LogMAR values were 0.78±0.15 in aniridia subjects and 1.40±0.88 in WAGR syndrome subjects (P=0.001). The mean LogMAR values for the better-seeing eye corresponded to Snellen visual acuity of 20/125 in aniridia subjects and 20/500 in WAGR syndrome subjects. This average visual acuity was worse than the threshold for profound visual impairment (WHO criteria) and legal blindness (AAO criteria) in WAGR syndrome but not in aniridia subjects. In analysis of both eyes, the visual efficiency was 34% in aniridia subjects and 2% in WAGR syndrome subjects. Visual acuity was significantly worse in WAGR subjects with multi-gene deletion mutations compared with aniridia subjects with nonsense mutations, which corresponded to differences in standard visual function thresholds. Our results suggest that visual acuity may indicate severity of ocular involvement and variability of phenotype in aniridia and WAGR syndrome.